Why We Vote : How Schools And Communities Shape Our Civic Life - Campbell, David E (Princeton University Press, 2006)
Why do more people vote--or get involved in other civic and political activities--in some communities than in others? Why We Vote demonstrates that our communities shape our civic and political engagement, and that schools are especially significant communities for fostering strong civic norms.